Bifunctional Protein Conferring Enhanced Green Fluorescence and Puromycin Resistance. (August 2001) - Abbate, J.; Lacayo, J.C.; Prichard, M.; Pari, G.; McVoy, M.A.
A new genetic marker was created in which sequences from enhanced green fluorescent protein were fused to those of puromycin N-acetyl transferase. The resulting fusion protein (EGFP-puro) conferred both green fluorescence and resistance to puromycin when expressed in mammalian cells. The utility of EGFP-puro as a selectable/screenable marker was demonstrated by the ease with which a recombinant guinea pig cytomegalovirus containing EGFP-puro was isolated by a combination of puromycin selection and screening for green fluorescence. We conclude that EGFP-puro is a compact and versatile marker that should prove useful for recombinant virus and transgenic cell line construction, particularly in applications in which coding capacity is limited.